SINKRETISASI SIWA-BUDDHA DI PURA YEH GANGGA DESA PEREAN TENGAH KECAMATAN BATURITI KABUPATEN TABANAN - Made Joniarta (Pangkaja: Jurnal Agama Hindu, 2023)
This research was conducted on the author's interest in the study of the Theology of Harmony in Bali. Harmony between religious communities in the middle of the island of Bali, not only by the national consensus on political and social stability, but also because of local wisdom about syncretization in the religious aspect. The Shiva teachings that dominate and as the most and even inspire most of the Hindu values in Bali do not forget to accommodate and harmonize themselves with other teachings, one of which is the Buddhist tradition. from that, the existence of Buddhism is still developing today. One of the reflections of the unification of the values of Shiva-Buddha teachings can be found at Pura Yeh Gangga, Central Perean Village. There are three problems discussed in this research, namely, (1) The Synchronization Process of Shiva-Buddha Teachings at Yeh Gangga Temple, (2) The driving factor for the implementation of Shiva-Buddha Synchronization, (3) Implications of the Synchronization of Shiva-Buddha Teachings at Yeh Gangga Temple.The theory used to dissect the formulation of the problem in this study is Durkheim's Socio-Cultural Evolution theory to dissect the problem of the Shiva-Buddha Synchronization Process at Yeh Gangga Temple and also to dissect problems regarding the driving factors for the implementation of Shiva-Buddha Synchronization and Hebert's theory of symbolic interaction. Blumer discusses the problem of the implications of the syncretization of Shiva-Buddha teachings in Yehgangga Temple. This research is a descriptive qualitative research. The primary data source in this research is Yeh Gangga Temple and Hindus and Buddhists as pengempon. Data collection was carried out using the snowball technique. The results of this study have occurred syncretization of Shiva-Buddha teachings at Yeh gangga Temple, including (1) the history of the Shiva-Buddha unification, (2) the arrival of Shiva-Buddha teachings in Central Perean Village, (3) the process of syncretizing the Shiva-Buddha teachings, and (4) Meru Tumpang Pitu as a form of syncretization. The driving factors for syncretization include (1) religious system factors, (2) social factors. The implications of the Shiva-Buddha teaching syncretization at Yeh gangga Temple include (1) Social Implications and (2) Theological Implications.